Description of Medical Career Choices during the COVID-19 Pandemic for Students of the Medical Profession Study Program, Faculty of Medicine, Tanjungpura University - Ninanda, Zahlah; Fitrianingrum, Iit; Pratiwi, Sari Eka (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2025)
Highlights: The most sought-after medical career choices and institutions were specialist doctors and hospitals. The most sought-after medical career choices were obstetrics and gynecology specialists.   Abstract Introduction: Government policies during the coronavirus disease (COVID-19) pandemic have limited the clinical rotation learning system of the Medical Faculty at Tanjungpura University. This study examined the description of medical career choices during the COVID-19 pandemic for students of the Medical Profession Study Program, Faculty of Medicine, Tanjungpura University. Methods: This was a descriptive study using a quantitative method in the form of a questionnaire. A total of 138 students were selected through the purposive sampling technique (n=138). The variables were then measured using a medical career choice questionnaire. The obtained data were further processed using the International Business Machines Corporation (IBM) Statistical Package for Social Sciences (SPSS) for Windows version 23.0 and Microsoft Excel 2013. Results: Study results showed that from 138 samples (n=138), students chose careers as general practitioners (male=17.5%; female=16%), specialist doctors (male=70%; female=73%), lecturers (female=2%), structural doctors (male=5%; female=6%), and non-medical careers (male=7.5%; female=2%). Regarding their preferred workplace, students chose the government hospital (male=40%; female=47%), private hospital (male=37%; female=32%), public health center (male=7%; female=9%), private clinic (male=5%; female=4%), state-owned clinic (male=3%, female=1%), military (male=5%, female=2%), ministry (male=3%; female=1%), educational institution (female=3%), and police (female=1%). Conclusion: The most sought-after medical career choices and institutions were obstetrics and gynecology specialists and hospitals. Factors that influenced the selection of a medical career were personal and professional characteristics, employment conditions, personal life, preclinical and clinical rotation phase, demands of postgraduate education, and family roles. Conducting further research to determine the factors that influence the choice of a medical career by using mixed-method research or qualitative interviewing is recommended.